Pengaruh Social Media Marketing, Influencer, dan Varian Produk Terhadap Keputusan Pembelian Melalui Kepercayaan - Asfawi, Kristiyani; Tuti, Meylani (Indonesian Journal Publisher, 2025)
This study aims to analyze the influence of social media marketing, influencers, and product variety on purchase decisions, with consumer trust as a mediating variable. The study population consists of Mako consumers who made purchases in December 2024. Using a purposive sampling approach, data were collected from 242 respondents. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS software. The findings indicate that social media marketing, influencers, and product variety significantly affect consumer trust. Furthermore, consumer trust serves as a strong mediating variable, reinforcing the relationship between these factors and purchase decisions. Among the independent variables examined, product variety has the most dominant influence, both directly and indirectly, on purchase decisions. These findings highlight the importance of an integrated digital marketing strategy, effective social media utilization, and credible influencer collaborations in building consumer trust and enhancing brand loyalty. Practically, this study recommends optimizing digital marketing strategies through engaging and relevant content, influencer partnerships, and continuous product innovation to improve brand competitiveness and consumer appeal.